Crossing thresholds: Critical information literacy pedagogy and the ACRL framework. Issue 3 (2nd July 2016) - Bauder, Julia; Rod, Catherine
ABSTRACT: The new Framework for Information Literacy is a dramatic break from the previous Association of College and Research Libraries (ACRL) Information Literacy Competency Standards, but it does not depart as radically from actual library practice. Many librarians have already been trying to help students acquire a deeper, more contextual understanding of "information" and research. In this article, we review some of the practice-based literature on information literacy instruction that reflects efforts to teach this more nuanced view of "information, " and we highlight examples of ongoing instructional practices from a number of college and university libraries that teach in ways that are compatible with the new Framework.